PEMBUATAN PHANTOM RADIOLOGI BERBAHAN DASAR KAYU LOKAL SEBAGAI PENGGANTI TULANG MANUSIA - Widya Mufida; Asih Puji Utami; Sofie Nornalita Dewi (Jurnal Imejing Diagnostik (JImeD), 2020)
Background: Phantom radiology is used as a medium of learning as a substitute for human bones. In its use this phantom radiology has economic value high enough to be an obstacle to the learning process. Therefore, it is necessary to make a phantom with basic materials that are easily accessible and have the same density value as human bones.Methods: the method used throughout this study is through an experimental approach. The research stage involves testing the density of wood by comparing the density value of the sample used, determining the composition of the mixture between wood, contrast media and adhesives that produces phantom with the density that most closely resembles bone phantom.Results: From the results of the research, the density value of the anthropomorphic phantom humerus was 9034, and the information obtained for the density value of the four wood phantoms with basal values. Based on the results of the calculation of the density value obtained the highest value on phantom 1 with a density value of 12775, phantom with the lowest density value of 7682, namely the second phantom, the value of wood phantom density is quite close to the density value of anthropomorphic humerus phantom, namely phantom 3 with a density of 8986 and Phantom 4 density which is slightly above the wood Phantom 2 density value is 7773.Conclusions: In this study to produce wood phantom with a density that resembles bone phantom is carried out with local wood base material mixed with BaSO4 contrast media, so that the average density value is 8986 close to the density value in anthropomorphic bone phantom humerus.